2022
DOI: 10.1155/2022/3530937
|View full text |Cite
|
Sign up to set email alerts
|

Peptidoglycan-Like Components in Z-100, Extracted from Mycobacterium tuberculosis Strain Aoyama B, Increase IL-12p40 via NOD2

Abstract: Background. Z-100 is a hot-water extract of the human-type Mycobacterium tuberculosis strain Aoyama B. While Z-100’s macrophage-mediated immunomodulatory effects have been reported, the mechanistic details have not been fully clarified. Here, we studied the immunomodulatory effects of Z-100 on mouse bone marrow-derived cells, human CD14+ cells, and skin. Methods. Mouse bone marrow-derived cells and CD14+ cells were cultured in the presence of granulocyte-macrophage colony-stimulating factor, differentiated int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…We previously reported that Z-100 increases IL-12p40 production [13]. Therefore, we examined whether the antitumor effects of Z-100 were abolished in IL-12p40 KO mice and found that, indeed, the antitumor effects of Z-100 were absent in these animals, as shown in Fig.…”
Section: Abolishment Of the Antitumor Effects Of Z-100 In Il-12p40 Ko...mentioning
confidence: 77%
See 4 more Smart Citations
“…We previously reported that Z-100 increases IL-12p40 production [13]. Therefore, we examined whether the antitumor effects of Z-100 were abolished in IL-12p40 KO mice and found that, indeed, the antitumor effects of Z-100 were absent in these animals, as shown in Fig.…”
Section: Abolishment Of the Antitumor Effects Of Z-100 In Il-12p40 Ko...mentioning
confidence: 77%
“…Immunotherapies that include an anti-PD-1 antibody have been reported to be highly effective against hot tumors [1,4,21], which may explain why the combination of Z-100 and anti-PD-1 antibody was effective in the report by Kobayashi et al [14]. Further, we previously reported that Z-100 increases IL-12p40 production [13]. IL-12p40 is known bind to IL-12p35 to form the heterodimer IL-12, which is involved in antitumor immunity [22].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations